Beach and Surge Flies (Diptera: Canacidae) from the Arabian Peninsula, with descriptions of three new species - Munari, Lorenzo (Zootaxa, 2008)
Three new species of Canacidae, Nocticanace affinis sp. nov., Xanthocanace hamifer sp. nov., and Suffomyia dancei sp. nov. are described and illustrated from the Arabian Peninsula (United Arab Emirates, Oman). Keys to the species of Arabian Canacinae and the world species of the genus Suffomyia are provided.